2003
DOI: 10.1037/0735-7044.117.2.195
|View full text |Cite
|
Sign up to set email alerts
|

An oxytocin antagonist infused into the central nucleus of the amygdala increases maternal aggressive behavior.

Abstract: Decreased oxytocin levels in the amygdalas of rat dams following chronic gestational cocaine exposure have been correlated with heightened maternal aggressive behavior. In this experiment, drug-naive dams were implanted with bilateral cannulas into the central nucleus of the amygdala (CNA) or control area and infused with 1,000 or 500 ng of an oxytocin antagonist (OTA) or buffer, 4 hr before testing. Behavior was compared among dams infused with OTA into target areas just outside the CNA and cocaine-treated da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
97
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 32 publications
10
97
1
2
Order By: Relevance
“…In animal models, gestational cocaine exposure leads to deficits in oxytocinergic activity, and to diminished maternal but increased aggressive behaviors, effects similar to those seen in dams treated centrally with an oxytocin antagonist rather than cocaine (Johns, Lubin et al, 1997;Johns, Noonan et al, 1997Lubin, Elliott et al, 2003). In the present investigation, mothers with gestational cocaine exposure reported more hostility and depressed mood, a trend towards more life stress over the past month, and less social support and sense of mastery and control in their lives.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In animal models, gestational cocaine exposure leads to deficits in oxytocinergic activity, and to diminished maternal but increased aggressive behaviors, effects similar to those seen in dams treated centrally with an oxytocin antagonist rather than cocaine (Johns, Lubin et al, 1997;Johns, Noonan et al, 1997Lubin, Elliott et al, 2003). In the present investigation, mothers with gestational cocaine exposure reported more hostility and depressed mood, a trend towards more life stress over the past month, and less social support and sense of mastery and control in their lives.…”
Section: Discussionsupporting
confidence: 66%
“…Mother rats that have higher rates of maternal behavior (licking and grooming their pups) than other dams also have markedly higher oxytocin receptor density in the amygdala (Champagne & Meaney, 2001). Significantly lower oxytocin levels are found in the amygdala during the postpartum period when rat mothers gestationally treated with cocaine are compulsively aggressive and aggression is significantly elevated in nontreated rat mothers when amygdaloid oxytocin receptors are blocked during the postpartum period Lubin, Elliott et al, 2003). Increases in oxytocin levels in brain regions of the postpartum rat, such as the medial preoptic area of the hypothalamus, ventral tegmental region, and amygdala, are associated with better maternal behavior and, for amygdala only, decreased aggression (Elliott et al, 2001;Johns et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, dams treated with cocaine gestationally were also found to exhibit differences in oxytocin system dynamics Johns, Lubin, Walker, Meter, & Mason, 1997;Johns, Nelson, et al, 1998;; Lubin, Elliott, Black, & Johns, 2003). Oxytocin is an important neuroendocrine system implicated in normal maternal behavior onset in rats (Fuchs, 1983;Pedersen et al, 1982;Pedersen, Caldwell, Johnson, Fort, & Prange, 1985;Pedersen et al, 1994) and therefore likely to be implicated when this behavior is disrupted (Pedersen et al, 1985; Van Leengoed, Kerker, & Swanson, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996). No reports, to our knowledge, have been published on intermittent gestational and postpartum cocaine treatment or the intergeneration effects of such treatment on maternal behavior.In previous studies, dams treated with cocaine gestationally were also found to exhibit differences in oxytocin system dynamics Johns, Lubin, Walker, Meter, & Mason, 1997;Johns, Nelson, et al, 1998;; Lubin, Elliott, Black, & Johns, 2003). Oxytocin is an important neuroendocrine system implicated in normal maternal behavior onset in rats (Fuchs, 1983;Pedersen et al, 1982;Pedersen, Caldwell, Johnson, Fort, & Prange, 1985;Pedersen et al, 1994) and therefore likely to be implicated when this behavior is disrupted (Pedersen et al, 1985; Van Leengoed, Kerker, & Swanson, 1987).…”
mentioning
confidence: 98%